Use of chronic lymphocytic leukemia-international prognostic index in patient risk stratification-single center experience - Trajkova, Sanja; Cevreska, Lidija; Krstevska -Balkanov, Svetlana; Pivkova -Veljanovska, Aleksandra; Popova-Labacevska, Marija; Jovanovska, Aleksandra; Ridova, Nevenka; Stojanovska, Simona; Panovska-Stavridis, Irina (International Journal of Research in Medical Sciences, 2021)
Background: Several prognostic factors have been identified to predict the outcome of patients with chronic lymphocytic leukemia (CLL). To predict the time to first treatment (TFT) we integrated the data of clinical and biological markers in CLL-International prognostic index (CLL-IPI). Aim of the study was the determination of the impact of CLL-IPI in prediction of TFS in CLL patents. Methods: The study was set up retrospectively and included 90 patients with CLL diagnosed and treated at the university clinic of hematology for a period of time from January 2012 to January 2020. We incorporated the data of Binet staging system, most adverse cytogenetic marker and mutational status of immunoglobulin heavy chain in CLL-IPI. Results: The statistical data of the 90 patients showed that the median TFS for low CLL-IPI (N=24), intermediate CLL-IPI (N=40), high risk CLL-IPI (N=17) and very high risk group (N=9) according to the CLL-IPI scoring system was 20.1, 17.6, 7.1 and 5.8 months, respectively. Multivariate analysis indicated that del 17p (p<0.008) was independent prognostic factors of TFS. Conclusions: CLL-IPI is a powerful risk stratification tool for CLL patients and this system has also provided treatment recommendations for different patient risk subgroups.